Stadslivet på Skärholmstorget - Eriksson, Kristina (2016)
The aim of this thesis was to take Skärholmstorget as an example of a place with a lot of outdoor activity and to clarify the reasons to why it has become like that. I wanted to use Gehls theories to analyse the preconditions for urban life with drawing as a tool in my analysis. My main question was: What landscape architectural solutions form the urban life at Skärholmstorget? Through the method I choose I explored that question by the following questions: What qualities that support urban life has Skärholmstorget got, according to Gehls theories? How can drawing as a method clarify Gehls conclusions in how the design of a place effects the activity. My method was to visit and read about Skärholmstorget and factors that support urban life and then investigate the place and analyse the preconditions for the outdoor activity. The analysis of activity was based on the theories that Gehl presents in the book Life between buildings: Using public space (2011). The analysis is divided in two parts; the urban planning of the square and the design of the square. By drawing different parts of the square I visualised the design to deepen my understanding of the forms meaning according to peoples activity. The result became an analyse of activity at Skärholmstorget. Reflections to a list of questions, maps of analysis and drawings with appurtenant texts show the result. There are several situations that support urban life both in the planning and in the design of the square. The analysis arrived at the conclusions that the variety of destinations there are to be found at Skärholmstorget in combination with a design that allows walking, standing and sitting creates the activeness. Even though the design was lacking in some terms of creating activity, people are gathering at the square and the visitors attract more visitors to come. I assume it has evolved such a self-reinforcing process, where some activity take place more events and people tend to join and new activity develops. The wide variety of functions and services on the square and the fact that there are no vehicular traffic give good conditions for activity in a planning perspective. In terms of the design the northern part of the square has qualities like good climate conditions, a smaller scale and details to move and linger by. These positive aspects that contribute to life between the buildings at Skärholmstorget can be used as inspiration when working as a landscape architect. Another result of this theses is the elaboration of a method of analysis where I assembled Gehls theories in a list of questions to investigate and developed the analysis of the design in another dimension by drawing different environments at the square. Drawing as a method helped me notice things like big respective intimate scales and how people interacted with different elements at the square.